Female directors in bank boardrooms and their influence on performance and risk-taking - Gulamhussen, M. A.; Santa, S. F. (Global Finance Journal, 2015)
We assess the role of women in bank boardrooms in a sample of 461 large banks from OECD countries. After controlling for bank and country specific effects, we find that the presence and percentage of female directors in boardrooms have a positive influence on performance. We also find a negative relation between the presence of women in boardrooms and risk-taking. These relations hold for the supervisory board, and with some exceptions for the audit committee. For a sub-sample of 134 listed banks we find that markets positively value the presence of women on the board, supervisory board and audit committee.